2012
DOI: 10.1371/journal.pone.0039163
|View full text |Cite
|
Sign up to set email alerts
|

The HCV Non-Nucleoside Inhibitor Tegobuvir Utilizes a Novel Mechanism of Action to Inhibit NS5B Polymerase Function

Abstract: Tegobuvir (TGV) is a novel non-nucleoside inhibitor (NNI) of HCV RNA replication with demonstrated antiviral activity in patients with genotype 1 chronic HCV infection. The mechanism of action of TGV has not been clearly defined despite the identification of resistance mutations mapping to the NS5B polymerase region. TGV does not inhibit NS5B enzymatic activity in biochemical assays in vitro, suggesting a more complex antiviral mechanism with cellular components. Here, we demonstrate that TGV exerts anti-HCV a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…To examine the inhibitory effect of directacting antivirals (DAAs), we exposed the replicons to various concentrations of danoprevir, an NS3 protease inhibitor, and 2=CMeA, an NS5B nucleoside polymerase inhibitor. Danoprevir and 2=CMeA are highly potent against genotype 1b replicons, with reported 50% effective concentrations (EC 50 s) of 1.8 nM and 0.2 to 0.5 M, respectively (20,52,54). Our results showed that genotype 2a and 4a replicons, with average EC 50 s of 65 and 1.2 nM, respectively, were sensitive to danoprevir, whereas the EC 50 for genotype 3a replicons was 900 nM, suggesting a lower inhibitory effect of danoprevir against genotype 3a (Fig.…”
Section: Subgenomic Replicons Of Hcv Genotypes 3a and 4amentioning
confidence: 99%
“…To examine the inhibitory effect of directacting antivirals (DAAs), we exposed the replicons to various concentrations of danoprevir, an NS3 protease inhibitor, and 2=CMeA, an NS5B nucleoside polymerase inhibitor. Danoprevir and 2=CMeA are highly potent against genotype 1b replicons, with reported 50% effective concentrations (EC 50 s) of 1.8 nM and 0.2 to 0.5 M, respectively (20,52,54). Our results showed that genotype 2a and 4a replicons, with average EC 50 s of 65 and 1.2 nM, respectively, were sensitive to danoprevir, whereas the EC 50 for genotype 3a replicons was 900 nM, suggesting a lower inhibitory effect of danoprevir against genotype 3a (Fig.…”
Section: Subgenomic Replicons Of Hcv Genotypes 3a and 4amentioning
confidence: 99%
“…The Palm II nonnucleoside inhibitors that are currently in different phases of development are given in Table 7. Tegobuvir has a unique mechanism of action and is distinct from other NNIs of NS5B [149]. Tegobuvir undergoes metabolic activation resulting in glutathione adducts which specifically interacts with NS5B thereby inhibiting viral replication [149].…”
Section: Site IV [Palm Ii]mentioning
confidence: 99%
“…Tegobuvir has a unique mechanism of action and is distinct from other NNIs of NS5B [149]. Tegobuvir undergoes metabolic activation resulting in glutathione adducts which specifically interacts with NS5B thereby inhibiting viral replication [149]. PPI-383 is a nonnucleoside inhibitor with pan-genotypic activity; it exhibits EC50 value of 8.3nM, 2.2nM against genotypes 1a and 1b respectively in cell-based replicon assays.…”
Section: Site IV [Palm Ii]mentioning
confidence: 99%
“…Cross-resistance analyses with the site III inhibitor A-782759 and site IV inhibitor HCV-796 revealed that Tegobuvir acts via a mechanism that is different from that of other non-nucleoside HCV polymerase inhibitors (Shih et al, 2011). Tegobuvir undergoes a CYP 1A-mediated intracellular activation step; the resulting metabolite, after forming a glutathione conjugate, directly and specifically interacts with and inhibits NS5B (Hebner et al, 2012). When administered in combination with Peg-IFN/RBV in treatment naive GT1 patients, Tegobuvir (40 mg BID) increased RVR (rapid virological response) by $30% and cEVR (complete early virological reponse) by $20% over Peg-IFN/RBV treatment although, no improvement in SVR was observed in the final analysis (Lawitz et al, 2011).…”
Section: Introductionmentioning
confidence: 99%